Principle of Time Stretching in Game Dynamic Problems - Chikrii, G.Ts. (Кибернетика и вычислительная техника, 2019)
The purpose of the paper is to deduce, sufficient conditions for termination of the games, for which Pontryagin’s condition does not hold, by the use of the effect of information delay, to specify these conditions for the case of integro-differential dynamics, and to illustrate the obtained result with the model example.